Contribuição à modelagem e análise do envelhecimento de transformadores de potência - Tereza Cristina Bessa Nogueira Assuncao (2007)
Power Transformers are important and expensive elements of a power system. Inadvertent failure of power transformers would cause long interruption in power supply with consequent loss of reliability and revenue of the supply utilities. Therefore, the importance of the premature detection of every process that can take to an imminent failure in the transformer. During the normal operation of the transformer, the electrical insulation is subjected to various kinds of stresses. The more important among them are electrical, thermal, mechanical and chemical. Each of these stresses, appearing singly, or in combination, would leave to an irreversible deterioration in the several properties of the insulation. Of the many parameters used as sensitive indices of the dynamics of insulation degradation, are the winding hot-spot temperature and the top-oil temperature, that given a fairly indication of the rate of degradation. Further, the accurate estimation of the temperatures would enable to determine the maximum loading of the power transformer. However, the model more used in the temperature calculations present limitations due to the difficulty of the mathematical modeling of a complex phenomenon as the flow of heat in a transformer, and mainly due to the variations of this parameters and of the thermal model caused by the aging, installation place and operation conditions. Different approaches are employed to tackle the problems of the temperature calculation, for example, techniques of the artificial intelligence such as, Artificial Neural Network and Least Squares Support Vector Machines (LS-SVM). Taking into consideration the observations done previously, in this work will be presented the calculation of the degree of polymerization, estimativeof the hot spot and top-oil temperature, calculation of the moisture in the oil/paper system of the transformers and estimate of the elapsed life of the power transformers. Thus, the objective of this work is the investigation of the consistent technologies for the evaluation of the operation conditions of the transformer, the articulation among the several applied methodologies and the proposition of a methodology for the monitoring of the process of the transformer aging.